A Multifunctional Hydrogel with Multimodal Self-Powered Sensing Capability and Stable Direct Current Output for Outdoor Plant Monitoring Systems - Xinge Guo; Luwei Wang; Zhenyang Jin; Chengkuo Lee (Nano-Micro Letters)
Highlights A simple and scalable fabricated hydrogel with multiple functionalities to realize self-sustainable outdoor monitoring solely by it for large-scale applications in precision agriculture. Stable direct-current output without requirement on stochastic or temporal environmental energies, achieving an energy density of 1.36 × 107 J m–3 with continuous operation of 56.25 days in normal outdoor environment. Self-powered noninvasive leaf relative water content monitoring and environmental sensing to evaluate plant health status with high durability and self-recoverability in severe environments.